Community Empowerment Participation in Forest Revegetation: An Analysis Study on the Slope Communities of Mount Arjuna, Indonesia - Nugroho, Matheus; Hermanto, Yustinus Budi (Jurnal Soeropati, 2023)
The research objectives was to determine the analysis of community empowerment participation for the forest revegetation in Arjuna Mount. This service uses a Participatory Rural Appraisal approach, with the study population covering communities around the forest of Arjuna Mount Pasuruan-East Java Indonesia. Data obtained from respondents with a questionnaire and analyzed using SEM (structural equation modeling), to find out an overview of respondents' responses about community participation in the preservation of the Arjuna Mount Forest. Community participation in the form of human capital, economy, social, local institutions, facilities and infrastructure has significant influence on community empowerment for the preservation of the Arjuna mount forest. Estimated regression weights for each indicator of community empowerment in Leduk, Jatiarjo and Dayurejo villages are human resources 0.99, economy 0.99, social 0.97, local institutions 1.00 and facilities and infrastructure 1.00. This explains that local institutional factors, facilities and infrastructure have a significant influence on community empowerment for the preservation of the Arjuna mount forest.